1986
DOI: 10.3354/meps032101
|View full text |Cite
|
Sign up to set email alerts
|

Plankton response following a spring upwelling event in the Ria de Arosa, Spain

Abstract: Phytoplankton and bacterioplankton growth dynamics, and biomass and ingestion rates of zooplankton and mussels hung from rafts in the Ria de Arosa, Spain, were studied after a spring upwelling event. Upwelling of North Atlantic Central Water was confirmed by salinity, temperature and nutrient properties of the bottom waters in the Ria and the positive upwelling index calculated for the study period. On 11 March. 1983, primary production and chlorophyll a concentrations exceeded 30 mg C m-3 h-' and 10 mg m-3, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
1

Year Published

1990
1990
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 12 publications
6
30
1
Order By: Relevance
“…Bacterial abundance values in this study are within the range found before at station 2 between January 1995 and December 1997 (0.6-30.6 x 10 5 cell ml -1 , Barquero, 1999), as well as within the range of the published values for other coastal areas in northern Spain (Hanson et al, 1986;Unanue et al, 1992;Tenore et al, 1995;Barquero et al, 1998;Morán et al, 1999;Barbosa et al, 2001;Varela et al, in press), with the exception of abundance values of highly eutrophic systems such as the Ría de Vigo (4.9-62.0 x 10 5 cell ml -1 , Zdawnoski and Figueiras, 1997). The relatively low variation in bacterial abundance when compared with other variables (e.g.…”
Section: Temporal Variationssupporting
confidence: 67%
See 2 more Smart Citations
“…Bacterial abundance values in this study are within the range found before at station 2 between January 1995 and December 1997 (0.6-30.6 x 10 5 cell ml -1 , Barquero, 1999), as well as within the range of the published values for other coastal areas in northern Spain (Hanson et al, 1986;Unanue et al, 1992;Tenore et al, 1995;Barquero et al, 1998;Morán et al, 1999;Barbosa et al, 2001;Varela et al, in press), with the exception of abundance values of highly eutrophic systems such as the Ría de Vigo (4.9-62.0 x 10 5 cell ml -1 , Zdawnoski and Figueiras, 1997). The relatively low variation in bacterial abundance when compared with other variables (e.g.…”
Section: Temporal Variationssupporting
confidence: 67%
“…) coincides with the minimum found by Tenore et al (1995) in samples from the Galician shelf, while the maximum production (145.2 mg C m -3 d -1 ) is higher than most values reported (1.0-3.8 mg C m -3 d -1 , Hanson et al, 1986;13.9-48.6 mg C m -3 d -1 , average of cold and warm season respectively, Unanue et al, 1992;0.1-28.7 mg C m -3 d -1 , Tenore et al, 1995;0.9-48.4 mg C m -3 d -1…”
Section: Temporal Variationsmentioning
confidence: 33%
See 1 more Smart Citation
“…the frequently observed correlation to measures of phytoplankton biomass or production), specific growth rates generally appear to be densityindependent (cf. , Hanson et al 1986). …”
Section: Structure Of the Pelagic Food Webmentioning
confidence: 99%
“…However, Alvarez-Salgado et al [1993] discuss the potential contribution of mineralization of organic matter outwelling from the rias contributing to the nutrient pool of the shelf waters. Mixing of intruded NACW with the lower-salinity waters in the rias occurs in the middle and inner Ria de Arosa [Hanson et al, 1986]. …”
Section: Mesoscale Spatial and Temporal Patterns In The Galician Shelmentioning
confidence: 99%